2009
DOI: 10.1139/f09-061
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics, overcompensation, and the source–sink status of marine reserves

Abstract: One of the hypothesized functions of marine protected areas (MPAs) is to serve as sources of biomass, with biomass spilling over from the reserve into neighbouring, harvested areas. We argue that the net larval flow (from or to the marine reserve) depends on between-area differences in the population-level biomass production rate, whereas the direction of adult flow depends on differences in the biomass standing stock. Hence, an important question is whether population-level biomass production increases (overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Our study suggests that natural populations may respond to increased mortality rates caused by infectious diseases or harvesting by stage-specific biomass overcompensation. This has management implications for at least two reasons: biomass overcompensation may result in counterintuitive measures necessary to restore fish stocks , and it may render marine protected areas less efficient than expected based on models without overcompensation (Claessen et al 2009). The populationlevel response depends on the increase in mortality rates, the competitive interactions within and between life stages, and the environmental conditions that determine resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that natural populations may respond to increased mortality rates caused by infectious diseases or harvesting by stage-specific biomass overcompensation. This has management implications for at least two reasons: biomass overcompensation may result in counterintuitive measures necessary to restore fish stocks , and it may render marine protected areas less efficient than expected based on models without overcompensation (Claessen et al 2009). The populationlevel response depends on the increase in mortality rates, the competitive interactions within and between life stages, and the environmental conditions that determine resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Changing basic assumptions of our model on resource growth, consumer foraging function, and energy allocation do not affect the presence of alternative stable states (Schreiber & Rudolf 2008, Claessen et al 2009, Guill 2009). Moreover, Guill (2009 demonstrated that the existence of alternative stable states only depends on the ability of both stages to have overcompensation at high biomass densities, a requirement fulfilled when there is only within-stage competition.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that management actions may have very different effects on exploited fish with stage-specific habitat shifts than on fish with habitat overlap throughout ontogeny. For example, the effectiveness of Marine Protected Areas (MPAs) in increasing overall abundance of harvestable life stages has been shown to depend on density-dependent interactions within other stages not of direct interest for management (Dugan & Davis 1993, St. Mary et al 2000, Claessen et al 2009). Processes within stages without commercial interest are thus also likely to influence fishing mortality effects in exploited stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B in the online edition of the American Naturalist). Understanding how assimilated energy is actually channeled in an organism is complicated, and numerous energy allocation rules have been proposed (Kooijman 2000;Claessen et al 2009). We assume that individuals follow a "net allocation model" (Kooijman 2000) before first reproduction and a "gross-production allocation model' (Kooijman 2000) after the first reproduction event (see app.…”
Section: Model Outlinementioning
confidence: 99%